Vermicomposting of Vegetable Wastes Using Cow Dung - K. Muthukumaravel; A. Amsath; M. Sukumaran (E-Journal of Chemistry)
Municipal solid wastes are mainly from domestic and commercial areas containing recyclable toxic substances, compostable organic matter and others. With rapid increase in population, the generation of municipal solid wastes has increased several folds during last few years. Disposal of solid wastes can be done by methods like land filling, incineration, recycling, conversion into biogas, disposal into sea and composting. Vermicomposting is one of the recycling technologies which will improve the quality of the products. The present study aims to find out the possibility of utilization of vegetable wastes for vermiculture. Earthworm Megascolex mauritii cultured in plastic trays (45 x 30 x 30 cm) containing soil alone (control) (T1), soil + cow dung (T2), soil + vegetable waste (T3) and soil + vegetable waste + cow dung (T4) for 60 days. Nutrient values were determined from the compost and compared with that of the control. From these results, it was found that NPK values were maximum in compost obtained from vegetable waste with the use of cow dung.